Radon in the environment - Wilkening, M. (Marvin) (Studies in environmental science, 1990)
Radon was discovered in 1900 but it was not until the 1950's that an awareness of its potential as a hazard to humans developed. This resulted primarily from a recognition of the high levels of exposure for uranium miners. Measurement of high concentrations of radon in homes led environmental health agencies to focus on radon as a health hazard and has resulted in concern from scientists, the medical profession and the general public. It is in this context that the author undertook the writing of this book. A need for a broader understanding of radon in the general environment in addition to that of indoors has become apparent. Since much of the author's research has to do with outdoor radon and its decay products, it seems appropriate to have a book available stressing studies on outdoor radon as well was that found indoors. This book is intended to fill a gap in our knowledge of radon concentration in the outdoor atmosphere as well as to provide results of previously published indoor measurements. In addition, work on radon decay product ion concentrations in these environments contributes a unique set of results on effects of radon and its decay products on the electrical characteristics of the atmosphere. These studies are important both from their significant contribution to human dose as well as their role in the atmospheric electrical environment.